Stocking density effect on growth and blood parameters of Dormitator latifrons (Richardson, 1844) - Badillo Zapata, Daniel; Tafoya Sánchez, Dayana Janeth; Vargas Ceballos, Manuel Alejandro; Ruiz-Gonzalez, Luis Eduardo; Rodríguez Montes de Oca, Gustavo Alejandro; Palma Cancino, David Julián; Vega Villsante, Fernando (Ecosistemas y Recursos Agropecuarios, 2022)
The native fish Dormitator latifrons culture technology in Latin America has increased, but the effect of high stocking densities on the physiology of the species is still unknown. The objective of this study was to analyze the effect of different stocking densities on growth and blood parameters. Wild organisms were acclimatized to culture conditions, and fed daily at 4% of total biomass, during 60 days. The weight and length of the organisms were recorded at the beginning and end of the experiment, growth and survival rates were determined. At the end of the experiment, a blood sample was taken from all fish for blood parameters evaluation. No differences in growth and survival were found between the different densities tested. Blood parameters were not affected by stocking density. All blood parameters are within the reference ranges indicating good fish health, except respiratory burst. The fish did not show signs of stress or any negative immune response at all culture densities tested.